INFLUENCE OF SAFETY STANDARDS AND GUIDELINES ON SAFETY TRAINING IN PUBLIC BOARDING SECONDARY SCHOOLS IN KITUI COUNTY, KENYA - Kimanthi, Moses Munyau; Mugwe, Dr. Mary; Thinguri, Dr. Ruth (African Journal of Education and Practice, 2019)
Purpose: There is a contemporary anxiety on the increasing cases of catastrophes in secondary schools in Kenya. The aim of this research was to explore the influence of safety standards and guidelines on safety training in public boarding secondary schools in Kitui County. Methodology: The study used securitization and disaster management theories. The investigation employed mixed methodology. The study embraced the concurrent triangulation design. This involved simultaneous data gathering but separate scrutiny of quantitative and qualitative data was done. The target population was 16,875 which included; 1,940 teachers and 14,903 students, 16 education officers and 16 senior police officers. The total sample was 650 participants. From 20 stratified sampled schools, 240 teachers and 400 students were used. From the education officers and police officers, 5 participants were used in each category. Principals and deputies were purposively sampled. Education officers and police officers were purposively sampled. Questionnaires with Likert scales were used. Interview schedules were used for education officers, police officers. Findings: From the research findings, it was clear that there was need to beef up security training in the learning institutions by having all teachers, students and non-teaching staff trained and fully equipped with disaster management skills such that they are able to combat calamities when they strike their institutions. Unique Contribution to Theory, Policy and Practice: The securitization and disaster management theories were used to warn and prepare for calamities consecutievely.The study established that training on catastrophe management was insufficient. The level of safety training was wanting. It was concluded that there was need to significantly implement training to enable security management in the schools. The theories were validated in that there was sensitization of disasters and the need to prepare in advance for calamities in schools. It was recommended that the government put in place curriculum for calamity training and schools prepare for disasters in advance.